Decorative alphabets and initials - Nesbitt, Alexander, 1901-1995. (New York, N.Y. : Dover Publications, 1987)
A sourcebook of initials and ornamental letters reproduces designs from the eighth century to the present.
Includes bibliographical references.
Keywords: Alphabets; Initials